On-Farm Relationships Between Agricultural Practices and Annual Changes in Organic Carbon Content at a Regional Scale - Dupla, Xavier; Lemaître, Téo; Grand, Stéphanie; Gondret, Karine; Charles, Raphaël; Verrecchia, Eric; Boivin, Pascal (Frontiers in Environmental Science, 2022)
Both soil quality degradation and climate change mitigation issues emphasize the need to increase, or at least stabilize, the topsoil organic carbon content (SOC) in arable land. This on-farm study aimed at measuring the impact of agricultural practices on changes in soil organic carbon (SOC) content over ten years. A total of 120 fields belonging to 120 farms representative of the cropping systems and soil properties in Western Switzerland (Lake Geneva region) was randomly selected. The field 0-20 cm topsoil was sampled at a 10-year interval, and the corresponding cropping practices were gathered using farmer’s interviews and the mandatory records of yearly practices at field level in Swiss-farms. Only 1) organic matter inputs and 2) cover-crop intensity were significantly correlated to SOC increase while 3) the soil tillage intensity and 4) the soil saturation in carbon expressed as a SOC to clay content ratio were correlated to SOC decrease. Among others, temporary meadows were not correlated to changes in SOC content mainly due to increased tillage and decreased cover-crops between meadows. Organic farming did not correlate either with SOC changes due to the large tillage intensity applied for weed control. The observed SOC changes ranged from -56‰ to + 74‰ and were well explained by a linear regression model with additive effect of the four identified SOC change factors. The additivity of these factors means that farmers can emphasize the methods of their choice when regenerating their soils. This study advocates that strict no-till is not required at low carbon saturation level (small SOC:Clay ratio). However, as carbon saturation increases, conservation tillage and then no-till practices become necessary to further increase SOC contents. These findings are in accordance with previous studies showing that SOC is currently increasing at more than +4‰ on average in the region and provide practical insights to further manage the transition of farming systems towards soil regeneration.